The impact of jawbone regions (molar area, premolar area, anterior area) and bone density on the accuracy of robot-assisted dental implantation: a preliminary study - Miadili, Mirealimu; Li, Xiaoman; Zhang, Yan; Ruan, Danping; Liu, Wei; Zhang, Jianfei; Gao, Yiming (Frontiers in Bioengineering and Biotechnology, 2025)
Robotic-assisted dental implantation represents a transformative innovation in modern dentistry, offering enhanced surgical precision and reduced variability. Despite its clinical adoption, the impact of anatomical and bone-related factors on placement accuracy remains underexplored. This retrospective study evaluated 54 implants placed in 30 patients using cone-beam computed tomography (CBCT) and virtual planning software to analyze deviations in crown position, apex position, and angulation. Significant regional variations in accuracy were observed, with higher angular deviations in the anterior maxilla (mean ± SD: 3.21° ± 2.22°) and greater positional deviations in the posterior mandible (1.09 mm ± 0.51 mm) (p < 0.05). Implant diameter significantly influenced global deviation (p = 0.019), while implant length and bone density (classified by Misch’s system) showed no significant effects (p > 0.05). However, denser bone types (D1) exhibited a trend toward increased deviations, potentially due to insertion resistance. These findings underscore the need for region-specific and bone-quality considerations in robotic-assisted implantation. Refining robotic navigation and feedback mechanisms is critical to optimizing accuracy, particularly in anatomically complex regions.